Strengthening Dairy Cooperative through National Development of Livestock Region - ., Priyono; Priyanti, A (Indonesian Animal Sciences Society, 2015)
Establishment of dairy cattle development region needs to be conducted in accordance with the national dairy industry development plan. Dairy cattle regions have been designed and equipped with infrastructure supplies, supporting facilities, technologies, finance, processing, marketing, institutional and human resources. Dairy cooperative is one of the marketing channels of milk and milk products which have strategic roles to support the national dairy industry. Collaborations between dairy cooperatives and smallholder farmers within a district region have to be done based on agricultural ecosystems, agribusiness system, integrated farming and participatory approach. This may improve dairy cooperatives as an independent and competitive institution. Strengthening dairy cooperatives in national region dairy cattle was carried out through institutional inventory and dairy cooperatives performance; requirement of capital access, market and networks as well as education and managerial training; certification and accreditation feasibility analysis and information and technology utilization. Establishment of emerging dairy cooperatives towards small and micro enterprises is carried out by directing them to establish cooperatives which have legal certainty and business development opportunities. The impact of strengthening dairy cooperative may support dairy cattle development through increase population and milk production. Sustainable dairy cattle development needs to be supported by regional and national government policies. Key words: Dairy cooperatives, animal husbandry district development, dairy